Pengaruh Pengajaran Kewirausahaan Terhadap Kemampuan Berwirausaha Alumni Akademi Komunitas MAPINDO - Ni Putu Oka Ariantini; Bagus Putu Ekadharma Susila (Journal Research of Management, 2024)
This study aims to analyze the impact of entrepreneurship education received by students of Akademi Komunitas Manajemen Perhotelan Indonesia on their entrepreneurial skills after graduation. Focusing on alumni from various study programs, the research employs a descriptive qualitative method to deeply explore the experiences and challenges faced by alumni in starting and managing their businesses. The sample consists of 10 randomly selected alumni, and data are collected through semi-structured interviews. Analysis is conducted using a thematic approach to identify patterns related to the application of entrepreneurial skills acquired during their studies. The results indicate that entrepreneurship education at the campus significantly contributes to enhancing the practical skills of alumni in entrepreneurship, such as the ability to identify business opportunities, manage risks, and innovate. Additionally, the majority of alumni reported that the entrepreneurship courses provided a strong foundation in business management and decision-making. However, the study also found that some alumni faced difficulties in applying theory to practice, especially in adapting to dynamic market conditions. These findings offer important insights for educational institutions to evaluate and develop entrepreneurship curricula to be more relevant and applicable to current industry needs. This research is expected to contribute to the field of entrepreneurship education, particularly in developing a more practical curriculum oriented towards creating competent entrepreneurs in the future